The economy is an organism? A study of metaphors in Malaysian business times - Tengku Mahmood, Tengku Farah Petri; Rafik-Galea, Shameem; Mohamad Ali, Afida; Mohd Kasim, Zalina (Malaysian Association of Modern Languages, 2013)
This article applies Conceptual Metaphor Theory developed by Lakoff and Johnson (1980) to investigate the metaphorical linguistic manifestations of the conceptual metaphor the economy is an organism based on Charteris-Black and Ennis’s (2001) proposed conceptual metaphor. This study is a non-experimental descriptive study, which uses the corpus linguistic approach for data collection and the corpus for analysis of 50 share market news reports that were randomly identified. An expert within the business context was appointed to provide expertise in the interpretation of specific types of data derived from the corpus. The findings demonstrate that the conceptual metaphor: the economy is an organism is widely used in the corpus collected. The findings show that the use of metaphorical linguistics expressions (MLE) resistance in a way concretizes the abstract concept of share prices as it evokes the image of share prices as an animate entity that can move forward and be stopped by a force (resistance). The analysis above therefore, supports Charteris-Black and Ennis’s (2001) conceptual metaphor, the economy is an organism.